Study on the Evaluation of the Practice of Building Survey for Maintenance of Public Building in South-East Nigeria - Osuagwu Andrew Chima; Nkeleme Emmanuel Ifeanyichukwu; Amafili Tochukwu Nnamdi; Ike Goodluck Chukwuemeka; Nzeneri Oluchukwu Precious-favour (Novel Perspectives of Engineering Research Vol. 3, 2021)
The maintenance of the public buildings is evasive without a conscious practice of building surveying as it avails the maintenance personal insight that informs the building maintenance this The research evaluates the practice of building in South-East Nigeria and its impact on the maintenance of public buildings. It was pursuit through the use of a structured questionnaire. Public buildings within Abia, Enugu, and Imo states of the study were studied with the respondent drawn from the users and officials in charge of the maintenance of the building. A total of 390 questionnaires were administered with 314 returned giving a response rate of 80.5%. A random sampling technique was adopted and the data was analyzed using a computer-based Software SPSS version 21. The result was presented using statistical tools Mean, Relative Importance Index (RII). From the result, there is no substantial development in the condition of public buildings in southeast states. In addition, the problems associate with building maintenance have significantly affected the building conditions in the study area. Adequate planning of maintenance work that is proactive and not corrective. Aging building parts should be replaced to avoid it making other parts of the building dilapidating. Government should ensure that most of the public buildings have a maintenance policy and there is effective communication between the maintenance department and the building occupants. Government should ensure that there is a condition survey for the public building adopting the approach of the framework developed in this study.